Implementation Of Value Added Tax Policy In E-Commerce Shopee - Nurul Hafifah; Gunadi Gunadi (Department of Public Administration, 2023)
Value Added Tax or Tax on Consumption is a tax imposed as a result of the delivery of taxable goods (BKP) or taxable services (JKP) in the customs area which is carried out with added value. The self-assessment tax collection system in Indonesia affects the VAT system by crediting or payment methods. This is related to the increasing number of online sales through e-commerce media in Indonesia, one of which has a significant effect on the drastic increase in revenue is Shopee. The purpose of this study is to determine the implementation of the existing VAT policy in e-commerce Shopee and what are its effects on the State. The method used in this research is qualitative with a literature study approach, the results of this study are that since the implementation of the Shopee collection in early 2020 until now, internal socialization is needed to business actors both those who already have a TIN and those who do not. Both the macro industry and micro MSMEs, so that the implementation of the policy of charging VAT to consumers will not affect service quality, satisfaction, and the number of requests through Shopee e-commerce. In addition, it is supported by a policy from Shopee which confirms that his appointment as a trade value added tax (VAT) collector through the electronic system (PMSE) according to PMK 48/2020 will not affect the selling price of goods.